Comparison of the Effect of Different Percentages of Sesame Oil and Soybean Oil on Growth Performance, the Weight of Internal Organs, and Serum Biochemical Parameters in Japanese quails - Maryam Karimi-Dehkordi; Forogh Mohammadi; Majid Gholami-Ahangaran (پژوهشهای تولیدات دامی)
Extended Abstract Background: Recently, the consumption of poultry meat, especially quail meat, has increased significantly due to some nutritional features, including high-quality protein and low fat content. This issue has led to an increase in the demand for the production of healthy products. Fat sources are one of the food items needed to provide energy in the poultry diet. Usually, mixed vegetable oils are used in commercial diets. Sesame oil has essential unsaturated fatty acids for poultry, which can have beneficial effects on the growth and health indicators of chickens. The main essential fatty acids in sesame oil include linoleic acid, oleic acid, palmitic acid, and stearic acid. The use of essential fatty acids in the diet of poultry increases their storage in meat and eggs, which can have beneficial effects on human health. Sesame oil contains compounds called lignans, such as sisamin, sisamulin, and small amounts of sisamol, and has many different physiological functions, such as reducing blood fat, reducing the level of arachidonic acid, increasing antioxidant capacity, increasing the bioavailability of gamma-tocopherol, and anti-inflammatory functions. On the other hand, sesame lignans can protect body cells from free radical damage by inhibiting reactive oxygen species. Sesame oil can increase the detoxification of chemicals in the liver and has a protective role against oxidative stress. Considering the antioxidant properties and nutritional compounds in sesame oil, the present study was conducted to investigate the effect of different levels of sesame oil and soybean oil on performance and growth indicators, as well as some serum biochemical parameters, including liver enzymes, profile fat, and proteins, in Japanese quail. Methods: Three hundred quails (Japanese quail) with the age of 10 days were randomly divided into five treatments with three replications (20 quails in each replication) and fed with experimental diets for 42 days. All groups were reared in the same growing and management conditions until 42 days of age. In the experimental treatments, the base diet containing zero (control), 25, 50, 75, and 100% sesame oil was used instead of soybean oil. Growth indices (weight gain, feed consumption, and feed conversion ratio, FCR), the weight of internal organs (liver, heart, gizzard, breast, and thigh muscle), and some serum biochemical parameters were measured at the end of the growing period. Serum biochemical parameters included total protein, albumin, globulin, triglyceride, cholesterol, LDL (low-density lipoprotein), and HDL (high-density lipoprotein). The concentrations of blood parameters were measured by colorimetry (photometry) using commercial kits available in the market and based on the provided instructions. The data were statistically analyzed by SPSS version 22 statistical software with the one-way analysis of variance (ANOVA) test. Statistical analysis was performed at a 95% confidence level. Results: Feed consumption and FCR decreased by increasing the percentage of sesame oil replacement. The lowest feed consumption during the growing period belonged to the groups receiving 75 and 100% sesame oil, and the highest feed consumption was recorded in the group receiving 100% soybean oil; these two groups showed a significant difference (p < 0.05). No significant difference was seen in the feed consumption between the other groups. The weight gain of quails at the end of the rearing period was not affected by different levels of sesame oil replacement. The comparison of FCR in different treatments showed that the lowest FCR was found in quails fed with 75 and 100% sesame oil, and the highest FCR was seen in quails receiving 100% soybean oil (p < 0.05). There was no significant difference in FCR between the other groups. Different levels of sesame oil and soybean oil did not significantly affect the weight of the internal organs of the studied quails. Total protein, albumin, globulin, and the ratio of albumin to globulin were not significantly different in all groups. Increasing the percentage of sesame oil decreased triglycerides, cholesterol, and LDL and increased HDL. The triglyceride level in the groups receiving 75 and 100% sesame oil was significantly lower than in the quails of the control group and those fed with 25% sesame oil (p < 0.05). Cholesterol levels were significantly lower only in quails receiving 75 and 100% sesame oil than in the other groups (p < 0.05). The LDL level in quails receiving 25 and 50% sesame oil was higher than in those receiving 75 and 100% sesame oil (p < 0.05). HDL also increased with increasing the percentage of sesame oil replacement. Conclusion: The results of this study showed that replacing sesame oil in the diet can have positive effects on the average daily feed intake and FCR. It seems that unsaturated fatty acids affect the digestibility and formation of fat micelles and lead to the improvement of metabolic energy efficiency, which affects the performance of quails. Furthermore, the addition of sesame oil to the diet improved serum biochemical indices, especially the lipid profile (triglyceride, cholesterol, LDL, and HDL). Probably, the sesamin present in sesame seeds reduces the activity and gene expression of enzymes involved in the synthesis of fatty acids and lipogenic enzymes and causes a decrease in liver fatty acid synthesis and ultimately the lipid profile. However, more studies should be considered to evaluate other effects of replacing this vegetable oil.